Educational open resources and teacher training - Vagula, Edilaine (Revista Hipótese, 2015)
The aim of this study was to analyze the possibilities of Open Educational Resources and its relevance in the teaching and learning, analyzing the results obtained from sixteen teachers, through a qualitative research and the use of the questionnaire. The results allowed us to analyze the basic education teachers’ directions on the production of knowledge through the REA. The findings point to the need for innovative methodologies, demonstrating its validity for the production of knowledge and the establishment of collaborative practices.